Philodendron guadarramanum (Araceae), a new species from Tabasco, Mexico - Díaz Jiménez, Pedro; Aguilar-Rodríguez, Pedro A.; Croat, Thomas B.; Cedeño-Fonseca, Marco; Alarcón Montano, Martin; Yovel, Yossi; Macswiney G., M. Cristina (Phytotaxa, 2020)
We describe and illustrate Philodendron guadarramanum, a new species of Araceae from Tabasco, Mexico. This species grows in montane cloud forest and evergreen tropical rainforest at elevations between 700 and 1100 m. It is similar to Philodendron purulhense, but differs from that species by having petioles broadly and sharply sulcate adaxially, with an acute medial rib, leaf blades with more basal veins and more primary lateral veins per side, and inflorescences more numerous per axil.